The Rural and the Urban: A Spatial Reading of Selected Poems by Stephen Spender and Badr Shakir al-Sayyab - Haitham K. Al-Zubbaidi; Khalid Qais Abd (Nalans)
The countryside and the city are considered among the most frequently tackled themes in British and Arabic poetry. They are viewed as two inseparable aspects of man’s life in the modern age. Many poets write about them because they appreciate the rural since it is still where man finds tranquillity, spontaneity and outlet from all urban life pressures. On the contrary, the city is presented as a place of stress, chaos, loss and instability. In the present paper, the main concern is to discuss selected poems by Stephen Spender (1909-1995) and Badr Shakr al-Sayyab (1926-1964) in terms of three intrinsic elements of space theorized by Henri Lefebvre,  a French Marxist philosopher and sociologist, along with Raymond Williams, to critically examine both Spender’s and al-Sayyab’s rendering of a variety of poetic devices to portray the countryside represented by the village with all its images, and the urban landscape defined by the city which is depicted in terms of corruption, pollution and isolation. It also aims to elucidate the essential components of space, applying modern poetry to the presentation of the countryside and the city to explicate how they are both oriented in Spender’s and al-Sayyab’s selected poems. One of the noteworthy conclusions is that both of them employ spatial practices and representational to portray the rural and urban images of life as conceived by the reader.